Two new species of the genus Deontolaimus de Man, 1880 (Nematoda: Leptolaimidae) from mangrove ecosystems of Vietnam - Tu, Nguyen Dinh; Thanh, Nguyen Vu; Hoang, Lai Phu; Saint-Paul, Ulrich (Zootaxa, 2016)
Two new species of the free-living marine nematode genus Deontolaimus (Leptolaimidae) are described from mangrove forests of the Can Gio Biosphere Reserve and Tien Yen, Quang Ninh, Vietnam. D. mangrovi sp. nov. is distinguished from D. papillatus de Man, 1880 and D. cangioensis sp. nov. by tail shape: conical and then elongated, without pointed tip. Deontolaimus cangioensis sp. nov. resembles D. papillatus in body shape, especially in the pointed tail terminus. D. cangioensis differs from D. papillatus in having a complicated gubernaculum with dorsally curved apophyses.